Efficacy and Safety of Elbasvir‐Grazoprevir Fixed Dose in the Management of Polytreated HCV Patients: Evidence From Real‐Life Clinical Practice. (10th May 2018) - Caroleo, Benedetto; Colangelo, Lidia; Perticone, Maria; De Sarro, Giovambattista; Gallelli, Luca
Abstract: Chronic hepatitis C virus (HCV) infection represents a global public health challenge, and new drugs have been authorized for its treatment. In this study, we evaluated both the clinical efficacy and safety of elbasvir‐grazoprevir fixed‐dose combination in HCV patients. We performed a prospective single‐blind study on patients admitted to the Regional Center for HCV Treatment of the University of Catanzaro from March 1, 2017, to December 31, 2017, in patients >30 years old with a history of chronic HCV infection. During the study period, we enrolled 29 HCV patients (18 women and 11 men; age, 62.5 ± 14 years, range 36‐82; HCV‐RNA: 2 384 859 ± 2 487 747 IU/mL, range, 60 400 − 8 930 000 IU/mL genotype 1b). In 28 of 29 patients (96.5%) we documented a rapid and complete remission of HCV infection 4 weeks after the beginning of the treatment, while in 1 patient it was reached in 8 weeks. During the study, we did not record any serious adverse drug reaction or drug interaction and no patients discontinued the treatment. However, 4 patients (13.8%) developed an asymptomatic plasma transaminase increase that appeared at 8 weeks after the beginning of the treatment and disappeared 4 weeks later in 3 patients and 8 weeks later in 1 patient. In conclusion, we documented that in real life the development of plasma transaminase increase in 4 elderly women >70 years old, suggesting that more attention must be focused on this age population.